Comparative Analysis of Students in Terms of Gender, Background of School, Student Enrollment (A Case study: Vocational Accounting Study Program) - Anggraeni, B D (KnE Social Sciences, 2018)
In this study, the authors have tried to analyze student-learning outcomes in terms of student’s gender, educational background in previous school and student force. This study compares the learning outcomes reflected in the Grade Point Average (GPA) obtained by students from three independent variables. The data used in this study is secondary data taken from the academic system. The student population in accounting study program, about 516 students, became the sample in this research. Analyzed the comparative test using the t-test for gender and one-way ANOVA test for testing on the background of the school’s department and student enrollment. The results of this study indicates a difference in learning outcomes between female and male students, but there is no difference between the school’s department and the student enrollment. Keywords: learning outcomes, gender, background of school, student enrollment